Unraveling The Countermeasures by The Social Service of Gorontalo Province Against The Exploitation of Children with Disabilities - Nurain Hunta (Estudiante Law Journal, 2020)
Abstract:This study is intended to (1) find out the role of the Gorontalo Provincial Social Service in overcoming the exploitation of children with disabilities as beggars in Gorontalo Province; (2) to find out what are the inhibiting factors for the role of the Gorontalo Provincial Social Service in overcoming the exploitation of children with disabilities in Gorontalo Province. This study uses empirical legal research methods, which use field facts as the main data in the research being conducted. The data sources used are primary data sources as the main data, and secondary data sources as supporting data consisting of documents and scientific works related to the problems being discussed. The sample used in this research is employees at the the Gorontalo Provincial Social Service, children with disabilities, and parents of children with disabilities. The results show first, the role of the Gorontalo Provincial Social Service is to provide legal protection to children with disabilities who are victims of exploitation as beggars with preventive legal measures consisting of socialization, strengthening of the companion team, and providing social assistance; and repressive legal efforts consisting of coaching and legal assistance. The second, the role of the Provincial Social Service to children with disabilities who are victims of exploitation also experiences obstacles such as the stubbornness shown by children with disabilities and their parents, the lack of competence of disability assistants, and the absence of regional regulations on disability in Gorontalo Province.Keywords: Legal Protection; Children with Disabilities; Exploitation